2022
DOI: 10.1186/s12890-022-02014-x
|View full text |Cite
|
Sign up to set email alerts
|

Body composition and risk factors associated with sarcopenia in post-COVID patients after moderate or severe COVID-19 infections

Abstract: Background Post-COVID-19 syndrome is characterized by diverse symptoms and abnormalities that persist beyond 12 weeks from the onset of acute COVID-19. Severity disease has been associated with more musculoskeletal alterations such as muscle weakness, dyspnea, and distance walking. The aim was to evaluate the impact of invasive mechanical ventilation (IMV) on body composition and investigate risk factors associated with sarcopenia in post-COVID-19 patients three months after moderate or severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Previous research showed a negative impact of PCS on body composition, muscle function, and quality of life [27]. In patients with PCS, rehabilitation has improved body composition, not only by increasing skeletal muscle mass but also by reducing fat mass and waist circumference [27,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research showed a negative impact of PCS on body composition, muscle function, and quality of life [27]. In patients with PCS, rehabilitation has improved body composition, not only by increasing skeletal muscle mass but also by reducing fat mass and waist circumference [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research showed a negative impact of PCS on body composition, muscle function, and quality of life [27]. In patients with PCS, rehabilitation has improved body composition, not only by increasing skeletal muscle mass but also by reducing fat mass and waist circumference [27,28]. Both the reduction in fat tissue and waist circumference are beneficial in terms of the risk of various chronic diseases, especially affecting the cardiovascular system [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Patients in ICU who had COVID-19 were inclined to be diagnosed with sarcopenia, compared to other patients hospitalized for COVID-19 [20,21] . Moreover, the risk of sarcopenia was higher among the patients after severe or moderate COVID-19 infection with prolonged length of hospital stay and invasive mechanical ventilation [22] . However, some studies indicated that sarcopenia was unrelated to mortality of COVID-19 [23,24] .…”
Section: Introductionmentioning
confidence: 94%
“…During 2 years of the COVID-19 worldwide pandemic, scientific researchers have focused on long-term morbidity from COVID-19. Although the scientific community’s understanding of long COVID-19 (LC) is still evolving, and understanding of the diagnoses, phenotypes, and epidemiology is nascent (Bell et al, 2021), LC’s health impacts and symptoms have been assessed by a broad range of studies (Aiyegbusi et al, 2021; González-Islas et al, 2022; Nalbandian et al, 2021). It is suggested that more than 20% of people positive for COVID-19 develop post-COVID-19 syndrome (Iqbal et al, 2021).…”
Section: Introductionmentioning
confidence: 99%